PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PT. CAHAYA TECHNOLOGY UNGGAS UNIT HATCHERY KABUPATEN PANDEGLANG - M. Azhar Putra Faris; Didi Sunardi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the influence of work discipline and organizational culture on Organizational Citizenship Behavior (OCB) at PT. Cahaya Technology Unggas Hatchery Unit, Pandeglang Regency. This study uses a quantitative approach with a survey method. The population in this study were all employees of PT. Cahaya Technology Unggas, with a sample of 61 respondents determined using a saturated sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, simple and multiple linear regression analyses, correlation tests, coefficient of determination tests, and hypothesis tests (t-tests and F-tests) with the help of the SPSS version 26 program. The results of the regression analysis showed that work discipline had a positive and significant effect on Organizational Citizenship Behavior with a t-count of 2.875 > 2.002. Furthermore, organizational culture was also proven to have a positive and significant effect on Organizational Citizenship Behavior with a t-count of 4.964 > 2.002. The results of the correlation test indicate a strong and positive relationship between work discipline and organizational culture with Organizational Citizenship Behavior with an f-value of 164.855 > 3.160. Meanwhile, the results of the coefficient of determination (R²) test indicate that work discipline and organizational culture are able to explain variations in Organizational Citizenship Behavior by 67.8%, while the remaining 32.2% is influenced by other factors outside this study. Partial and simultaneous hypothesis testing proves that all hypotheses proposed in this study are accepted. Thus, improving work discipline and strengthening organizational culture can be an important strategy in improving employee Organizational Citizenship Behavior at PT. Cahaya Technology Unggas.